Comparing predictors of part‐time and no vocational engagement in youth primary mental health services: A brief report. Issue 4 (19th May 2017) - Cairns, Alice J.; Kavanagh, David J.; Dark, Frances; McPhail, Steven M.
Abstract : Aim: This investigation aims to identify if correlates of not working or studying were also correlated with part‐time vocational participation. Methods: Demographic and vocational engagement information was collected from 226 participant clinical charts aged 15 to 25 years accessing a primary youth health clinic. Multinomial logistic regressions were used to examine potential correlates no and part‐time vocational engagement compared to those full‐time. Results: A total of 33% were not working or studying and 19% were part‐time. Not working or studying was associated with secondary school dropout and a history of drug use. These associations were not observed in those participating part‐time. Conclusions: This result suggests that the markers of disadvantage observed in those not working or studying do not carry over to those who are part‐time. Potentially, those who are part‐time are less vulnerable to long‐term disadvantage compared to their unemployed counterparts as they do not share the same indicators of disadvantage.